Pengaruh Return Of Aset, Return Of Equity, Dan Earning Per Share Terhadap Harga Saham Pada PT Siantar Top Tbk - olivia yolanda; Sepia Ejayanti; Seresika Hana Pramesti (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2022)
This research was conducted to see the effect of the profitability ratios shown through Return on Assets, Return on Equity, and Earnings per Share on the company value of PT Siantar Top Tbk. indicated by the stock price. Selection of PT Siantar Top, Tbk. This is done because it sees the company's growth trend which continues to increase every year. Where sales is one of the important things used to see the probability ratio of the company. The research data used is secondary data taken from the financial statements of PT Siantar Top, Tbk. period 2014-2021. The results of the study show that partially ROE has no effect on the stock price of PT Siantar Top, Tbk. But the results of the study show that partially ROA and EPS have an effect on stock prices. And overall, ROA, ROE, and EPS affect the share price of PT Siantar Top, Tbk. Therefore, investors can look at the overall ROA, ROE and EPS values to decide whether to invest in PT Siantar Top, Tbk or not.